WIRAUSAHA MASA DEPAN: ANALISIS KEPRIBADIAN KEWIRAUSAHAAN MAHASISWA BISNIS - Sisilia, Kristina (Fakultas Ekonomi Universitas Islam 45, 2017)
A successful entrepreneur has to get an entrepreneur personality. This personality may encourage someone to make decision about starting their own business. Students who choose to enroll in a business school hope to have sufficient business knowledge to start a new business during or after their graduation. This research analyzes entrepreneurial personality of business students. The personalities are focus on entrepreneurial interest, motivation, and tolerance for ambiguity and risk tolerance using descriptive qualitative method. The results show that business students? characteristics have a very good entrepreneurial interest and motivation in business but their ambiguity and risk tolerance are at moderate level. It means that they dare to start business, make business decisions and activities, and aware of the losing capital and time as the potential risks.